THE MAIN FOUNDATIONS OF PHYSICAL REHABILITATION IN SOCIALIZATION OF CHILDREN WITH VISUAL IMPAIRMENTS (Education in the 21st Century, 2023)
In the article, the main foundations of physical rehabilitation in the socialization of children with visual impairments influence onto the lifespan of persons with blindness or low-vision. They try to move, interact with others less. This naturally brings to occurrence of secondary development disorders, they become passive, introverted and have difficulties of integration with these peers.The above mentioned determines the importance and significance of study of the physical rehabilitation in socialization of children with visual impairments and definition of the main foundations, that should be necessarily considered in the organization and implementation of this work with children who are blind or low-vision. This will become the basis for active involvement of these children in the socialization and every day active life. This defines the relevance of the studied problem, its theoretical, practical and social significance.